PERAN SHALAT DHUHA BERJAMAAH DALAM MEMPERKUAT SPIRITUALITAS DAN DISIPLIN SISWA SDIT SALSABILA AL MUTHI’IN BANGUNTAPAN YOGYAKARTA - Khairul Abdillah Harahap; Sofia Yunus Putri; Sabarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the implementation of congregational Dhuha prayer at SDIT Salsabila Al Muthi’in Banguntapan and its impact on students’ spirituality and discipline. Employing a qualitative descriptive approach, data were gathered through observations, interviews, and documentation involving principals, teachers, and students. The findings indicate that the institutionalization of Dhuha prayer effectively strengthens students’ spiritual consciousness, sincerity, and emotional tranquility while fostering time discipline, responsibility, and adherence to school regulations. The integration of worship routines into the school culture demonstrates a holistic character-building process rooted in Islamic values. These results align with recent studies emphasizing religious habituation as a pivotal framework for cultivating moral behavior and emotional resilience in students. The research contributes to expanding the theoretical understanding of religious habituation in Islamic education and offers a practical model for other Islamic schools seeking to strengthen character formation through daily religious practices.